When One and One Gives More than Two: Challenges and Opportunities of Integrative Omics - Choi, Hyungwon; Pavelka, Norman (Frontiers in Genetics, 2012)
Since the dawn of the post-genomic era a myriad of novel high-throughput technologies have been developed that are capable of measuring thousands of biological molecules at once, giving rise to various ‘–omics’ platforms. These advances offer the unique opportunity to study how individual parts of a biological system work together to produce emerging phenotypes. Today, many research laboratories are moving towards applying multiple omics platforms to analyze the same biological samples. In addition, network information of interacting molecules is being incorporated more and more into the analysis and interpretation of these multiple omics datasets, which provides novel ways to integrate multiple layers of heterogeneous biological information into a single coherent picture. Here, we provide a perspective on how such recent ‘integrative omics’ efforts are likely going to shift biological paradigms once again, and what challenges lie ahead.